Financial Analysis and Investment Strategies in the Luxury Goods Sector: A Comparative Study of LVMH, Hermès, and Richemont - Zheng, Chunyue (Transactions on Economics, Business and Management Research, 2024)
With the evolution of globalization and economics recovery after COVID in recent years cross the world, it is an obvious trend that people are willing to pay more to enjoy high quality of their lives. It indicates more business opportunities in luxury industry than ever to meet those consumer needs. To enable a solid understanding for financial investors in this segment with data-based business analysis, it is worthwhile to provide an investment proposal supported by a key benchmark analysis. Therefore, this paper summarizes an in-depth financial analysis of three luxury goods companies who are the leaders in the market, i.e. LVMH, Hermes, and Compagnie Financière Richemont SA (CFRS). The study is to aim an objective and concise assessment focus on the risk, profitability, and market ratios of these three companies to provide guidance to potential investment decisions. Financial indicators, including risk coefficients, profitability indexes, and market ratios, are analyzed to conclude with the investment strategies for six major investor profiles. The findings offer a comprehensive view with data supporting for different types of investors according to their customized financial preference and risk management to optimize their portfolios in the luxury goods sector.